The shaping of Ulster Presbyterian belief and practice, 1770 - 1840 - Holmes, Andrew R. (Oxford University Press, 2006)
Introduction -- Part I : Time -- The Lord's day -- Days of fasting and thanksgiving -- Calendrical customs and alternative beliefs -- Part II : Public worship in the meeting house -- Psalmody -- Preaching -- Communion and discipline -- Part III : Rites of passage -- Baptism -- Marriage and sexual relationships -- Death -- Part IV : Religious instruction, fellowship, and activity beyond the meeting house -- Catechizing, education, and reading practices -- Family worship, prayer meetings, and lay involvement in church life -- Conclusion